2013
DOI: 10.1074/jbc.m112.442616
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-regulated Kinase and Glycogen Synthase Kinase 3β Regulate Gephyrin Postsynaptic Aggregation and GABAergic Synaptic Function in a Calpain-dependent Mechanism

Abstract: Background: Molecular mechanisms of plasticity at GABAergic synapses are presently unclear. Results: ERK phosphorylates gephyrin at Ser-268 to regulate size of gephyrin postsynaptic scaffold and strength of GABAergic transmission. Ser-268 phosphorylation by ERK is functionally coupled to Ser-270 phosphorylation by GSK3␤ to determine calpain action on gephyrin. Conclusion: Multiple signaling cascades regulate gephyrin postsynaptic clustering. Significance: Dynamic modulation of gephyrin clustering by phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
143
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(150 citation statements)
references
References 30 publications
6
143
1
Order By: Relevance
“…The critical involvement of gephyrin in these mechanisms is consistent with several recent data highlighting its implication in the clustering of GABA A Rs. Phosphorylation of gephyrin on Ser270 by glycogen synthase kinase 3β (GSK3β) or on Ser268 by ERK have been shown to modulate the density and size of gephyrin clusters (8,31). Also gephyrin can interact with various partners, including neuroligin 2, collibystin, or even Cdc42 to regulate cluster formation and GABA A R aggregation (7,9).…”
Section: Discussionmentioning
confidence: 99%
“…The critical involvement of gephyrin in these mechanisms is consistent with several recent data highlighting its implication in the clustering of GABA A Rs. Phosphorylation of gephyrin on Ser270 by glycogen synthase kinase 3β (GSK3β) or on Ser268 by ERK have been shown to modulate the density and size of gephyrin clusters (8,31). Also gephyrin can interact with various partners, including neuroligin 2, collibystin, or even Cdc42 to regulate cluster formation and GABA A R aggregation (7,9).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation [29][30][31][32] , palmitoylation 33,34 and acetylation 35,36 of gephyrin have been reported and these post-translational modifications have been shown to affect the structure, trafficking, half-life and importantly the ability of gephyrin to interact with partner proteins. To test whether the identified short GABA A Rderived peptide fragments a9-11 also mediate binding to native full-length gephyrin comprising post-translational modifications, the peptides were covalently immobilized on iodoacetyl-activated beads and subsequently incubated with mouse brain lysates.…”
Section: Resultsmentioning
confidence: 99%
“…Puzzlingly, one study showed that protein phosphatase 1 directly interacted with gephyrin and that gephyrin clustering was decreased by the application of broad-spectrum phosphatase inhibitors, 45 whereas two other studies conversely found that the dephosphorylation of gephyrin increased gephyrin clustering. 43,44 In this context, it seems noteworthy that acute application of tumor necrosis factor-α downregulates inhibitory synaptic transmission via the protein phosphatase 1-dependent trafficking of GABA A receptors. 46 In addition to phosphorylation, gephyrin is subject to palmitoylation 47 (Figure 1).…”
Section: Posttranslational Modificationsmentioning
confidence: 99%
“…However, gephyrin has been identified as a phosphoprotein when copurified with the GlyR (which has kinase activity), 40 and mass spectrometric analyses of rat and mouse brains revealed that gephyrin has 22 phosphorylation sites, most of which are located within the C domain (except for threonine 324, which lies in the E domain 25,[41][42][43] ) (Figure 1). These modifications might induce conformational changes by affecting the structure of the C domain or the neighboring G and E domains, thereby altering the clustering, trafficking and binding properties of gephyrin.…”
Section: Posttranslational Modificationsmentioning
confidence: 99%
See 1 more Smart Citation